Effect of a ward-based outreach team and adherence game on retention and viral load suppression - Sanele Ngcobo; Steve Olorunju; Tshifhiwa Nkwenika; Theresa Rossouw (AOSIS, 2022)
Background: Only 66% of South African people living with HIV (PLWH) are virologically suppressed. Therefore, it is important to develop strategies to improve outcomes. Objectives: Assess the effect of interventions on 12-month retention in care and virological suppression in participants newly initiated on antiretroviral therapy. Method: Fifty-seven clinics were randomised into four arms: Ward-based primary health care outreach teams (WBPHCOTs); Game; WBPHCOT-Game in combination; and Control (standard of care). Sixteen clinics were excluded and four re-allocated because lay counsellors and operational team leaders failed to attend the required training. Seventeen clinics were excluded due to non-enrolment. Results: A total of 558 participants from Tshwane district were enrolled. After excluding ineligible participants, 467 participants were included in the analysis: WBPHCOTs (n = 72); Games (n = 126); WBPHCOT-Games (n = 85); and Control (n = 184). Retention in care at 12 months was evaluable in 340 participants (86.2%) were retained in care and 13.8% were lost to follow-up. The intervention groups had higher retention in care than the Control group, but this only reached statistical significance in the Games group (96.8% vs 77.8%; relative risk [RR] 1.25; 95% confidence interval [CI]: 1.13-1.38; P = 0.01). The 12 month virologic suppression rate was 75.3% and was similar across the four arms. Conclusion: This study demonstrated that an adherence game intervention could help keep PLWH in care. What this study adds: Evidence that interventions, especially Games, could improve retention in care.